Scale to Measure the Utilization of Farm Implements by the Farmers - S.D. , Patil; Shinde, S. B. (Indian Journal of Extension Education, 2016)
Farm mechanization helps to enhance the overall productivity and production with the lowest cost of production. In the  context of increasing commercialization of agriculture, mechanization is very important. But all the farmers may not  utilize the improved farm implements at the same time and at the same rate. It is very important to know the extent of  utilization of farm implements by the farmers. However, a systematic evaluative study on utilization of farm implements  by the farmers unfortunately has not drawn sufficient research attention which again is due to non availability of a scale to  correctly measure the farm implements utilization. Hence, an effort was made to construct and standardize a scale to  correctly measure the utilization of farm implements by the farmers. The study was conducted in Newasa, Rahuri, Karjat  and Pathardi tahsils of Ahmednagar district and Pandharpur, Malshiras, Karmala and Mohol tahsil of Solapur district. The  method of identification of the parameters, framing and scoring of the parameters and relevancy analysis was followed in  the construction of the scale along with testing of its reliability and validity. The scale developed was found to be highly  reliable and valid to measure the utilization of farm implements by the farmers. Also it can be used to measure the extent of  utilization of farm implements by the farmers beyond the study area with suitable modifications if required.
Keywords: Relevancy; reliability; validity; utilization; farm implements; scale